Po divné krajině : charakteristika a vnitřní členěni fantastické literatury - Dědinová, Tereza, 1982- (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2015)
The best works of fantasy tell stories about our world, about human consciousness and its boundaries. Their shift beyond the limits of the natural world and space-time allows a direct, clearer, and larger perspective. Through symbols, metaphors, and allegory, fantasy tackles universal issues and problems of our world. However, fantasy is a priori criticized as trivial, escapist literature not worthy of the time of a picky reader. As such, it is often relegated to the sidelines and gets only limited feedback. The ambition of this study is therefore to initiate a broader discussion about the phenomenon of fantasy literature and to draw attention to the issue of its reflection.